2018
DOI: 10.1186/s12889-018-5286-z
|View full text |Cite
|
Sign up to set email alerts
|

Triglycerides and total cholesterol concentrations in association with IFG/IGT in Chinese adults in Qingdao, China

Abstract: BackgroundTo investigative the association of triglycerides (TG) and total cholesterol (TC) concentrations with impaired fasting glucose/ impaired glucose tolerance (IFG/IGT) in Chinese adults.MethodsThe population-based cross-sectional diabetes survey was conducted in 2006 and 2009 in Qingdao, separately. 4400 participants (1 793 men and 2607 women) were include in current analysis. IFG/IGT was defined according to fasting plasma glucose (FPG) and/or 2 h post-load plasma glucose (2 h PG). Logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…It was demonstrated by cohort studies that WC was an independent factor that is associated with the risk of cardiovascular diseases [5658]. On the other hand, a significant relation was available between TG concentrations and insulin resistance [59] and the increased TG was independently associated with the risk of hypertension, diabetes, and IFG [60, 61]. Moreover, TG was demonstrated to be significantly associated with VAT in healthy men, even after controlling for SAT [62].…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated by cohort studies that WC was an independent factor that is associated with the risk of cardiovascular diseases [5658]. On the other hand, a significant relation was available between TG concentrations and insulin resistance [59] and the increased TG was independently associated with the risk of hypertension, diabetes, and IFG [60, 61]. Moreover, TG was demonstrated to be significantly associated with VAT in healthy men, even after controlling for SAT [62].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, LDL significantly did not increase linearly with age, which is in contrast to a population study in the United States. In overweight people, with increasing BMI, the level of LDL-C tends to be flat or decreased in males ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study also found that elevated TG and TC was in association with metabolic syndrome. 33,34 Lanaspa et al, 35 have suggested that HUA is more prone to develop fatty liver, which generated elevated TG and TC. In addition, there are few mechanisms between uric acid metabolism and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%